2020
DOI: 10.3390/biom10101460
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Deep Learning Based Multi-Omics Parallel Integration Survival Subtypes in Lung Cancer Using Reverse Phase Protein Array Data

Abstract: Mortality attributed to lung cancer accounts for a large fraction of cancer deaths worldwide. With increasing mortality figures, the accurate prediction of prognosis has become essential. In recent years, multi-omics analysis has emerged as a useful survival prediction tool. However, the methodology relevant to multi-omics analysis has not yet been fully established and further improvements are required for clinical applications. In this study, we developed a novel method to accurately predict the survival of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…Bioinformatics analysis showed that the expression levels of six of the 25 genes (ERO1B, DPY19L1, NCAM1, RET, MARCH1, and SLC7A8) were associated with survival in LUAD patients, and pathway analysis indicated that major cancer signaling pathways were altered in the subtypes. Expanding on this method, we identified survival-related subtypes of non-small cell lung cancer from six categories of TCGA multi-omics datasets (miRNA, mRNA, DNA methylation, somatic mutation, copy number variation, and reverse phase protein array) [106]. As a result, the subtype named the Integrated Survival Subtype, which combined the six types of data, successfully separated the poor and good prognosis groups of lung cancer patients with a statistically significant difference.…”
Section: Application Of Machine Learning and Deep Learning Techniquesmentioning
confidence: 99%
“…Bioinformatics analysis showed that the expression levels of six of the 25 genes (ERO1B, DPY19L1, NCAM1, RET, MARCH1, and SLC7A8) were associated with survival in LUAD patients, and pathway analysis indicated that major cancer signaling pathways were altered in the subtypes. Expanding on this method, we identified survival-related subtypes of non-small cell lung cancer from six categories of TCGA multi-omics datasets (miRNA, mRNA, DNA methylation, somatic mutation, copy number variation, and reverse phase protein array) [106]. As a result, the subtype named the Integrated Survival Subtype, which combined the six types of data, successfully separated the poor and good prognosis groups of lung cancer patients with a statistically significant difference.…”
Section: Application Of Machine Learning and Deep Learning Techniquesmentioning
confidence: 99%
“…In addition, there is a growing need for multimodal analysis, such as integrated analysis of genomic and epigenomic data, not just data from one modality. This kind of advanced analysis using a large amount of data is difficult to perform using conventional statistical methods, but nowadays, by proactively introducing artificial intelligence (AI) with machine learning (ML) and deep learning (DL) technologies at its core, good results can be obtained (29)(30)(31). In our view, there are four properties of ML and DL that are of particular importance.…”
Section: Introductionmentioning
confidence: 99%
“…One solution to this problem is the use of multi-omics analysis. Even if the appropriate data type required is unknown, the combination of one or more data types may prove useful [ 11 , 12 ]. However, there remains the problem that it is impossible for humans to find principals and make a decision because of too much information.…”
Section: Introductionmentioning
confidence: 99%